Anxiety and self-confidence levels of elite South African crawl stroke swimmers and its relationship with performance - Grobbelaar, H.; Coetzee, B.; de Ridder, J. H. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
Optimally developed psychological skills are regarded as important determinants of sport success. The effect of certain skills, such as anxiety and self-confidence on swimming performance has received considerable attention in the literature [1-4]. Unfortunately, little information exists on the current sport psychological skill levels of South African swimmers, and the effect thereof on their performances. The purpose of this study was, therefore, firstly to determine the somatic and cognitive anxiety as well as the self-confidence levels (and the perceived effect of these constructs towards performance) of elite crawl stroke swimmers. The second purpose was to determine the correlation between these constructs and the performances of these swimmers. Methods 27 swimmers (15 male, 19.0±3.36 yrs, 12 female, 17.7±2.45 yrs) were tested during the 2001 South African National Swimming Championships. The Competitive State Anxiety Inventory-II (CSAI-II, [5]) with an additional perception scale as well as a general questionnaire were used to gather information regarding the type and frequency of sport psychological skills used by these swimmers. Results No significant gender differences were observed for any of the measured construct levels. Statistically significant correlations were revealed for the females, pertaining to the perceived effect of somatic (200m) and cognitive anxiety (400m & 800m) on performance. The results of the female swimmers are reported in Table 1. Conclusion These findings support the notion that swimmers do not spend enough time on the psychological preparation for swimming competitions, even though it is indicated as important determinants of success. It emphasises the role that coaches, Sport Scientists and Sport Psychologists need to play in the development of a broad range of optimally developed sport psychological skills for enhanced swimming performances.